2017
DOI: 10.22159/ijpps.2017v9i10.20788
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Callinectes Chitosan as a Superdisintegrant in Metronidazole Tablet

Abstract: Objective: The objective of this study is to evaluate callinectes chitosan as a superdisintegrant in tablet formulation; superdisintegrants are incorporated into tablets at concentrations below 5% of tablet weight to effect prompt break-up of tablets after administration. Methods:Chitosan was extracted from shells of Callinectes gladiator. The polymer was characterized and then used as a disintegrant (in comparison with Ac-Di-Sol ® and corn starch) at concentrations of 2, 4 and 8% for the formulation of metron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
3
0
2
Order By: Relevance
“…The materials used include metronidazole powder (Hopkins and Williams, England), Merck Art 2330 microcrystalline cellulose (E. merck, Darmstadt), and chitosan obtained from shells of Callinectes gladiator having degree of deacetylation of 62.7% and viscosity of 2.88 mPas at 2% concentration, spindle #1, and 60 rpm [ 11 ]. Others are α -lactose monohydrate (Riedel De Haen Seelze, Hannover), magnesium stearate (BDH Poole, England), and talc (BDH Poole, England).…”
Section: Methodsmentioning
confidence: 99%
“…The materials used include metronidazole powder (Hopkins and Williams, England), Merck Art 2330 microcrystalline cellulose (E. merck, Darmstadt), and chitosan obtained from shells of Callinectes gladiator having degree of deacetylation of 62.7% and viscosity of 2.88 mPas at 2% concentration, spindle #1, and 60 rpm [ 11 ]. Others are α -lactose monohydrate (Riedel De Haen Seelze, Hannover), magnesium stearate (BDH Poole, England), and talc (BDH Poole, England).…”
Section: Methodsmentioning
confidence: 99%
“…Several authors have reported a significant in vitro/in vivo correlation (IVIVC) between data obtained with the flow-through cell and human behaviour [8,9], which makes it a suitable option to estimate the release of the drug in the human body. On the other hand, in vitro dissolution studies with new metronidazole formulations have been reported, including release data with USP Apparatus 4 [10][11][12]. The aim of this work was to test four metronidazole commercial formulations, three generic drug products and the reference under the hydrodynamic environment of the flow-through cell (USP Apparatus 4) and dissolution media of physiological relevance (pH 1.2, 4.5, and 6.8) to document whether these formulations meet standard criteria to waiver in vivo studies and consider them pharmaceutical equivalents.…”
Section: Fig 1: Chemical Structure Of Metronidazolementioning
confidence: 99%
“…Hal ini disebabkan fakta bahwa ketika kitosan dalam jumlah tinggi, penyerapan air ke dalam tablet menghasilkan pembentukan gel dari pada disintegrasi. Hasil ini konsisten dengan penelitian yang menunjukkan waktu hancur meningkat dengan konsentrasi kitosan 27 .…”
Section: Evaluasi Mutu Fisik Odt Paracetamolunclassified
“…Setiap formula memenuhi persyaratan bahwa tidak kurang dari 80% bahan harus larut dalam waktu 30 menit 13 . Tingkat kelarutan konsisten dengan literatur; semakin rendah laju disolusi, semakin besar kandungan kitosan 27 . Hal ini berkorelasi dengan laju disintegrasi, semakin cepat tablet larut semakin cepat proses disolusinya 29 .…”
Section: Evaluasi Mutu Fisik Odt Paracetamolunclassified